Sub-Patent Innovation Rights: Utility Models Petty Patents and Innovation Patents Around the World (Cambridge University Press, 2025)
The first book-length study of utility models and other forms of sub-patent protection across jurisdictions in Europe, the Americas, Asia, Oceania and Africa, critically assessing how they are utilized by innovators, litigants and dealmakers, and how they have impacted current debates over legal harmonization, innovation and economic development.